Causations of Failure in Megaprojects: A Case Study of the Ajaokuta Steel Plant Project - Olatunji, Oluwole (Higher Education Press, 2018)
This paper uses project organizational theories to draw lessons from a historic megaproject, the Ajaokuta Steel Plant (ASP). Archival reports on the ASP were explored to identify the unique attributes of the project; the political wrangling that underplayed its evolution, its economic significance and organizational impacts. Findings suggest the goals of the ASP project were, and still are, unambiguous. Failure occurred as socio-political forces aggravated the project’s complex milestones. Stakeholders were impatient with pre-project investigations. During planning, owners ignored opinions that were contrary to their expectations. While delays lingered, pressures from the global economy weakened the project’s motivation to succeed. These combined to turn the project’s outcomes into a chaotic situation that triggered dire implications. Despite about 1400% overrun in cost, the success achieved on the plant was 28% at commissioning. Contractors remained on site until eight years after commissioning. Six key elements of the 482 items in the ASP project contract were not delivered nearly 40 years on. A simplistic look at these suggests poor planning is the main problem. However, planning issues is not entirely strange in greenfield projects. The paper draws strength from project organization theories to explain what was poor about the planning. Socrates’ generic management theory was used to explain the role of leadership in the failure of the ASP project. McGregor’s Theory X and Theory Y explain the significance of stakeholders’ integration in megaprojects. Systems and chaos theories were used to explain the sensitivity of the ASP project to uncertainties. Narratives on these combine well to inspire stakeholders of megaprojects on where and how to seek courage in making effective plans that can help achieve success in complex projects. While normative literature only recognizes project success in a definitive perspective, this study provides insights from failure as an instrument to trigger sublime reflections.